Título Padrão: O documentário na sala de aula - da Cunha Neta, Leonor Moura; Santos-Marques, Ivoneide Bezerra de Araújo; Santos, Alana Driziê Gonzatti dos (Revista de Letras, 2022)
Considering the results of evaluations that measure the Basic Education Development Index (IDEB) of students from public schools, revealing that many of them are completing the last cycle of basic education without reaching the desired level of proficiency in Portuguese; also considering the discussions about what and how to teach in the classes of this curricular component, this article aims to discuss the role of literacy projects (KLEIMAN, 2000) in working with the discursive genres of the Brazilian Portuguese Language Olympiad (OLP), in this case, the documentary, a genre inserted in the sixth edition of the OLP, in 2019. Theoretically, this study is fundamentally anchored in the Bakhtinian conception of language and in literacy studies (KLEIMAN, 1995; 2000; SOARES, 2009; SANTOS, 2008; STREET, 2014; OLIVEIRA; TINOCO; SANTOS, 2011). From the methodological point of view, the research was configured as action research, developed in a qualitative and interpretive approach. Sixty-one students from two second-year classes of the New High School at the Alcides Wanderley State School in the city of Carnaubais, Rio Grande do Norte, participated in the research. The results show that reading, writing and rewriting practices during the production of short films enabled the development of multiple literacies. In addition, the work with the documentary genre contributed to the formation of critical thinking, to the development of creativity and agency of the students, in a collaborative and meaningful perspective of learning, capable of motivating students for pedagogical activities and reflection. criticism about what they learned, how they learned it and what they learned in school for what they learned, to better prepare them for the exercise of citizenship and social participation.